Nice Try, Bill, But … There You Go Again - Van De Ven, Andrew H.; Johnson, Paul E. (Academy of Management Review, 2006)
Bill McKelvey's commentary is provocative, but four points need correction. (1) The purpose of engaged scholarship is not just to advance practice but to create scientific knowledge. (2) Bill's food chain metaphor mistakenly views the gap between science and practice as a knowledge transfer problem. (3) Bill ignores the impact of biases of researchers by only focusing on practitioner bias. (4) He considers differing views of researchers and practitioners as antithetical; we view them as complementary.